Hotel guests’ intention to engage in green activities / Fauziah Deraman - Deraman, Fauziah (2012)
The development of hotel industry in Malaysia is increasing. There were always new hotels entering the hotel business in order to cater the increasing number of tourists. However, the development of hotel also poses potential dangers to the environment. This is because hotel consumed large amount of water and electricity and it is potentially damaging the environment. Thus, it is very crucial for hoteliers as well as the guest to participate in green initiatives in response to this issue. The current study adapted the model of Theory Planned Behavior in order to determine the relationship between environmental concern, social norms and reward with hotel guests’ intention to engage in green activities while staying at the hotel. The study surveyed 381 hotel guests’ at the selected hotels in Kuala Lumpur. There were 180 respondents that completed the survey for a 47% response rate. Survey questionnaires were used in order to gain the data from the respondents. The result shows that all the predictors had a positive relationship with intention to engage in green activities. In addition to that, among these predictors environmental concern was found to give more contribution to the intention. It was then, followed by social norm and rewards. Nevertheless, these three predictors only contributed 34% of predictors to the intention in this study. The other 66% were cause by other predictors that was not mention in the current study but can be added to the model for future research. Other predictors that could be added to the future study includes attitude towards green, perceived behavioral control as well as demographic data. It is worth to conduct a study on these predictors that may contribute to the intention to engage in green activities since it had been proved by previous researches. Moreover, the study only included respondents from Kuala Lumpur to answer the questionnaire and the results cannot be generalized. This was due to different locations of study with the same measurement scale were produced different results. The study also looked at the managerial implications for the lodging industry and make suggestions for the future research.